A longitudinal study of brain atrophy and cognitive disturbances in the early phase of relapsing-remitting multiple sclerosis. Issue 6 (1st June 2001) - Zivadinov, R; Sepcic, J; Nasuelli, D; De Masi, R; Bragadin, L Monti; Tommasi, M A; Zambito-Marsala, S; Moretti, R; Bratina, A; Ukmar, M; Pozzi-Mucelli, R S; Grop, A; et al.
Abstract : OBJECTIVE: ( a ) To establish whether the cognitive decline of the early phase of relapsing-remitting multiple sclerosis depends on the progression of the burden of disease, or on the loss of brain parenchyma, or is influenced by both; ( b ) to monitor the loss of brain parenchyma in the early phase of the disease; and ( c ) to examine its possible relation with the progression of physical disability. METHODS: For 2 years 53 patients with clinically definite relapsing-remitting multiple sclerosis with disease duration 1–5 years and expanded disability status scale⩽5.0 at baseline were monitored. The neuropsychological performances, the psychological functioning, the neurological impairment, and the disability have been assessed at baseline and after 2 years. Patients also underwent PD/T2 and T1 weighted brain MRI. T2 and T1 lesion volumes were measured by a semiautomatic technique. Quantification of brain parenchymal volumes was obtained using a highly reproducible computerised interactive program. The relation between cognitive impairment and MRI findings has been investigated by partial correlation and stepwise multiple regression analyses excluding the effects of age, education, anxiety, depression, and total days of steroid use. RESULTS: In the 2 years of the study the mean change for T2 and T1 lesion volumes and brain parenchymal volumes were +1.7 ml (95% confidence interval (95% CI) 1.3–2.2, p=0.005, (29.8%); +0.2 ml, 95% CI 0.15–0.26, p=0.004, (25%); and –32.3 ml, 95% CI 24.2–42.3, p<0.0001, (2.7%), respectively. Overall, 14 patients (26.4%) were judged to be cognitively impaired at baseline and 28 (52.8%) at the end of the follow up. Of the 18 neuropsychological tests and subtests employed in the study, patients with multiple sclerosis failed 5.8 (SD 2.3) tests at the baseline and 8.4 (SD 2.9) (p<0.0001) tests at the end of the study. When the cognitive changes were examined in individual patients, five (9.4%) of them were considered cognitively improved, 33 (62.3%) remained stable, and 15 (28.3%) worsened over 2 years. T2 and T1 volume changes in improved, stable, and worsened patients did not show any significant difference, whereas brain parenchymal volume decrease in cognitively worsened patients was significantly greater (−66 ml (5.4%), 95% CI 37–108.9, p=0.0031). The cognitive impairment was independently predicted over 2 years only by the change of brain parenchymal volumes ( R =0.51, p=0.0003). Ten patients (18.9%), who worsened by one or more points in the EDSS during the follow up period had significant decreases in brain parenchymal volumes (−99 ml (8%), 95% CI 47.6–182.3, p=0.005). At the end of the study the loss of brain parenchyma correlated significantly with change in EDSS ( r = 0.59, p<0.0001). CONCLUSIONS: In the early phase of relapsing-remitting multiple sclerosis the cognitive deterioration relies more on the development of brain parenchymal volume atrophy than on the extent of burden of disease in the brain. The loss of brain parenchymal volume underlies the progressive accumulation of physical disability from the initial phase of the disease, which becomes more demonstrable only if studied with longer observation periods. Probably, the main pathological substrate of brain atrophy in the early stage of the disease is early axonal loss, which causes the progression of neurological deficits and the development of cognitive impairment. These data support the debated opinion that disease modifying therapy should be initiated as early as possible.